Uma trajetória singular? Apontamentos sobre europeização, privatização e especificidades do ensino superior português - Antunes, Fátima (2017)
This paper proposes a script for discussing the recent trajectory of (public) higher education in Portugal highlighting structuring dynamics, based on studies, data and empirical research available: from expansion to exogenous privatization; from Europeanisation driven by the Bologna Process and the managerial Modernization Agenda to the structural adjustment policies promoted by the EU; from prolonged underfunding to the diversification of financing sources and the privatization within the public sector, with attention to certain aspects of teacher’s work and academic condition. Based on this debate some arguments are advanced in order to support a perspective about the multifaceted singularity of this trajectory